Use of 3D printing models for donor tooth extraction in autotransplantation cases - Rui Hou; Xiaoyong Hui; Guangjie Xu; Yongqing Li; Xia Yang; Jie Xu; Yanli Liu; Minghui Zhu; Qinglin Zhu; Yu Sun (BMC Oral Health, 2024)
Abstract Objective To clarify whether the 3D printing model has auxiliary functions in toto extraction of donor tooth in autotransplantation cases. Methods Two hundred and sixty patients who would have operation of ATT were divided into two groups. In group 1, determination of the tooth extraction in toto was predicted only according to the clinical and imaging examination. In group 2, the prediction was performed according to the clinical and imaging examination as well as the 3D model of donor tooth pre-extraction. A prespctive clinical study was designed on intra-group comparison between the predicted and actual donor teeth situation when extraction in cases of ATT. The consistent rate for the predicted results and the actual results were compared with the two groups. Results A remarkable difference was observed between the predicted results and the actual results of tooth positions and root numbers in group without model (p < 0,05). The consistency rate of the model group (94.62%) was significantly higher than that of non 3D model group (86.15%) (p = 0.034). Conclusion The 3D printing model for the donor tooth is helpful for dentists to predict the accuracy of toto extraction of donor teeth in autotransplantation cases.